Cert Prep: Unity Certified Associate Game Developer Materials and Lighting. - Thorn, Alan (linkedin.com, 2021)
Preparing for the Unity Certified Associate: Game Developer exam? Tune into this course to review the concepts covered on the materials and lighting portion of the test.